2012
DOI: 10.1007/s11033-012-2035-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between the OGG1 Ser326Cys and APEX1 Asp148Glu polymorphisms and lung cancer risk: a meta-analysis

Abstract: The previous published data on the association between the 8-oxo-guanine glycosylase-1 (OGG1) and apurinic/apyrimidinic-endonuclease-1 (APEX1/APE1) polymorphisms and lung cancer risk remained controversial. Several polymorphisms in the OGG1 and APEX1 gene have been described, including the commonly occurring Ser326Cys in OGG1 and Asp148Glu in APEX1. This meta-analysis of literatures was performed to derive a more precise estimation of the relationship. A total of 37 studies were identified to the meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 50 publications
1
9
1
1
Order By: Relevance
“…Extending this observation, we, in a large Han Chinese population, examined three common polymorphisms in RAGE gene and found that carriers of mutant genotypes of promoter polymorphism rs1800625 and coding polymorphism rs2070600 in 3rd exon exhibited strikingly increased risk for lung cancer, which was further potentiated by our following haplotype analyses. More recently, a systematic review of 3491 lung cancer patients and 4708 controls detected significant association of Asp148Glu (rs1130409) polymorphism with lung cancer, especially in Asian populations [16], in agreement with the results of our single-locus analyses. In this context, it is reasonable to hypothesize that genetic defects of RAGE and APE1 genes might increase the risk of developing lung cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Extending this observation, we, in a large Han Chinese population, examined three common polymorphisms in RAGE gene and found that carriers of mutant genotypes of promoter polymorphism rs1800625 and coding polymorphism rs2070600 in 3rd exon exhibited strikingly increased risk for lung cancer, which was further potentiated by our following haplotype analyses. More recently, a systematic review of 3491 lung cancer patients and 4708 controls detected significant association of Asp148Glu (rs1130409) polymorphism with lung cancer, especially in Asian populations [16], in agreement with the results of our single-locus analyses. In this context, it is reasonable to hypothesize that genetic defects of RAGE and APE1 genes might increase the risk of developing lung cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Two analyses focusing on a single locus suggested that the 1349 T>G polymorphism was not associated with lung cancer risk among Asians or Caucasians [21,23]. This result contrasts with another analysis, in which the number of studies was obviously smaller than a former and the current meta-analyses, suggesting an increased lung cancer risk in Asians [22]. The divergency highlights that it is worthwhile to carry out an extremely large-scale study to establish the association with high confidence.…”
Section: Discussioncontrasting
confidence: 72%
“…The majority of published studies have evaluated the impact of polymorphisms in relatively small populations. Most importantly, meta-analyses of lung cancer risk in relation to the aforementioned polymorphisms either using a single locus or including limited data also generated substantially inconsistent results [20][21][22][23]. We therefore conducted a more comprehensive evaluation of the hypothesis that HAP1 polymorphisms predispose to lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Increased risk among smokers [94,95] Increased resistance to cisplatin OR: 1.342 [96] 83.3% (20 out of 24) of cisplatin-resistant tumors show high APE1 expression levels [97] …”
Section: Thr 656 Gly Increased Expressionmentioning
confidence: 99%
“…Required for the repair of DSBs [16,17,103,104] Mutated Lower expression providing a better outcome in lung cancer patients [105] Increase in resistance to a wide range of DNA-damaging agents and radiation therapy [106][107][108][109] Low expression of BRCA1pS1423 was associated with a worse survival [110] atM ATM acts as a central mediator of the radioprotective machinery, participating in cellular stress responses, control of cell cycle checkpoints, repair of DSBs, and initiation of apoptosis Ser 62160 Gly>Ala Higher risk of lung cancer than those with the G allele OR: 1.6 [111] Ser 227060 T Increased risk of lung cancer OR: 1.55 [112] Ser 170548 C Increased risk of lung cancer OR: 1.51 [112] p53 Plays a role in apoptosis, genomic stability, and inhibition of angiogenesis [94][95]113] Frequently mutated or inactivated, including homozygous deletions and abnormally sized messenger RNAs, as well as a variety of point or small mutations Mutations lead to poorer patient prognosis and decreased survival [114] Ku70/80 Involved in numerous cellular processes including apoptosis, regulation of specific gene transcription, regulation of heat shock-induced responses and telomere maintenance [115][116][117][118] Ku70 (rs2267437) Increased risk of lung cancer OR: 1.32 [119] …”
Section: Brca1mentioning
confidence: 99%